Self-healing, anti-freezing, adhesive and remoldable hydrogel sensor with ion-liquid metal dual conductivity for biomimetic skin - Zhou, Zixuan; Qian, Chunhua; Yuan, Weizhong (Composites science and technology, 2021)
Flexible wearable sensors assembled from conductive hydrogels have received great attention due to their wide application in human-machine interfaces, medical and healthcare detection. However, the traditional conductive gel needs to be attached to the application surface with external force, and only respond to the single strain stimulus. Moreover, due to the existence of water, ordinary hydrogels cannot work at below zero temperatures, which severely limits the application of hydrogel-based flexible electronic devices. The flexible wearable epidermal sensors assembled by ultra-sensitive polyvinyl alcohol-tannic acid-eutectic gallium-indium (PVA-TA-EGaIn) hydrogels with adhesiveness, rapid self-healing, high electrical conductivity and mechanical properties, and temperature sensitivity. The rigid conductive hydrogel prepared by freeze-thaw cycles shows outstanding tensile/compressive strength (1.13 MPa/4.59 MPa) and toughness (1.9 MJ/m3), and reveals excellent fatigue resistance. It also exhibited high conductivity (3.63 S m−1) and strain sensitivity (gauge factor = 2.59). In addition, the hydrogels maintained good flexibility and conductivity at −10 °C. Besides, the PVA-TA-EGaIn hydrogels shows remoldability, which greatly prolongs the service life of the gel. The composite hydrogels show the potential of building the next generation of multifunctional hydrogel-based flexible wearable sensors in human motion monitoring, voice recognition and medical diagnosis. [Display omitted] •The high conductivity of the hydrogel was supplied by NaCl and EGnIn.•The hydrogel displayed outstanding self-healing and anti-freezing performance.•The hydrogel was endowed with self-adhesiveness and remoldability.•The flexible multifunctional sensors could be used as smart biomimetic skin.